Incidencia del Art. 168 numeral 6 de la constitución de la República del Ecuador en la aplicación del sistema oral en los juicios civiles en el juzgado sexto de lo civil, mercantil y laboral del cantón Pasaje, en el año 2012. - Chiriboga Gonzáles, José Alfredo (2013)
Through the revision of the bibliographic information, the scope and limitations of orality as a guiding principle of the processes have been exposed, exposing in turn the idea of ​​contradiction and concentration as technical supports of orality.